IPD-OUM Certificate Presentation Ceremony - Anuwar Ali, (Open University Malaysia (OUM), 2004)
Speech of the President/Vice-Chancellor OUM, Prof Tan Sri Anuwar Ali on Collaboration with Jaya Jusco at OUM Campus. 10 June 2004.